Myanmar's Transition : Openings, Obstacles and Opportunities - Cheesman, Nick (Book collections on Project MUSE., 2012)
With the world watching closely, Myanmar began a process of political, administrative and institutional transition from 30 January 2011. After convening the parliament, elected in November 2010, the former military regime transferred power to a new government headed by former Prime Minister (and retired general), U Thein Sein. With parliamentary processes restored in Myanmar's new capital of Naypyitaw, Thein Sein's government announced a wide-ranging reform agenda, and began releasing political prisoners and easing press censorship. Pivotal meetings between Thein Sein and Aung San Suu Kyi led.